2017
DOI: 10.1002/1878-0261.12072
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib induces activation of AMPK and inhibits hepatocellular carcinoma in a CDK4/6‐independent manner

Abstract: Palbociclib, a CDK4/6 inhibitor, has recently been approved for hormone receptor‐positive breast cancer patients. The effects of palbociclib as a treatment for other malignancies, including hepatocellular carcinoma (HCC), are of great clinical interest and are under active investigation. Here, we report the effects and a novel mechanism of action of palbociclib in HCC. We found that palbociclib induced both autophagy and apoptosis in HCC cells through a mechanism involving 5′ AMP‐activated protein kinase (AMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…It was reported that CDK4/6 inhibitors induce autophagy 29‐35 . Based on the results described above, we speculated that the prominent vacuole formation in response to abemaciclib might be related to autophagy.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…It was reported that CDK4/6 inhibitors induce autophagy 29‐35 . Based on the results described above, we speculated that the prominent vacuole formation in response to abemaciclib might be related to autophagy.…”
Section: Resultsmentioning
confidence: 53%
“…This observation also supports the idea that a target or targets other than CDK4/6 contribute to lysosomal dysfunction. Several previous studies reported induction of autophagy in response to CDK4/6 inhibitors 29‐34,50 . In this study, we sequentially monitored autophagic flux using fluorescence probe 37 ; this analysis revealed that all 3 CDK4/6 inhibitors tested inhibited autophagic flux at early time points.…”
Section: Discussionmentioning
confidence: 81%
“…All these suggest that autophagy is associated with the cell death induced in cells treated with palbociclib alone or in combination with SAHA. A previous study showed that palbociclib induced autophagy in hepatocellular carcinoma cells in a CDK4/6 independent manner, but through a mechanism involving 5′ AMP-activated protein kinase (AMPK) activation and protein phosphatase 5 (PP5) inhibition (62). Some earlier studies reported HDAC inhibitors could induce caspase-independent autophagic cell death in HeLa and chondrosarcoma (63,64).…”
Section: Palbociclib-resistant Npc Cells Were Sensitive To Cisplatinmentioning
confidence: 99%
“…Thus, Palbociclib has not only a cytostatic effect but seemingly a potential cytotoxic effect on CMT cells. Although this observation contrasts to that for human BCa cells, which showed no apoptosis after prolonged Palbociclib treatment, cytotoxic potential for the CDK4/6 inhibitor was reported for human glioblastoma, hepatocellular carcinoma and T‐cell acute lymphoblastic leukaemia cells . Wang et al demonstrated that the pro‐apoptotic Palbociclib effect is associated with CDK6 expression in that Palbociclib induces apoptosis in cancer cells with high expression of CDK6, whereas cells with low CDK6 only show cell cycle arrest .…”
Section: Discussionmentioning
confidence: 90%
“…Thus, CF41 cells apparently resist the cytotoxic mechanisms of Palbociclib longer than P114 cells. Palbociclib induces apoptosis of tumour cells by interfering with enzymes regulating glucose metabolism in T‐ALL cells or activation of AMP‐activated protein kinase in hepatocellular carcinomas . Assuming that Palbociclib also affects the viability of CMT cells through such mechanisms, different susceptibilities of these target enzymes might be responsible for the delayed effect on P114 and CF41 cell viability.…”
Section: Discussionmentioning
confidence: 99%